Assessing nursing mothers' knowledge, perceptions and uptake of Sulphadoxine Pyrimethamine (IPTp-SP) during pregnancy in the Ho Teaching Hospital of the Volta Region of Ghana. - Verner N Orish; Prince N Puplampu; Sylvester Y Lokpo; Precious K Kwadzokpui; Virtue Fiawokome De-Gaulle; Aleksandra Marinkovic; Stephanie Prakash; Rochelle Annan; Chuku Okorie; Adekunle Sanyaolu (Public Library of Science (PLoS), 2023)
Intermittent preventive therapy during pregnancy with Sulphadoxine Pyrimethamine (IPTp-SP) is one of the potent strategies for preventing malaria in pregnancy (MiP). Factors such as the pregnant woman's knowledge and very importantly perception or belief about IPTp-SP remains key determinant of IPTp-SP uptake. This study assessed the knowledge and perception of nursing mothers and their uptake of IPTp-SP during pregnancy in the Ho Teaching Hospital. We administered a close-ended questionnaire to 303 nursing mothers and obtained their sociodemographic details as well as information on their knowledge and perception of IPTp-SP utilization. We also reviewed the nursing mothers' antenatal care (ANC) booklets to ascertain the number of times IPTp-SP was taken during pregnancy. Pearson chi-square was used to determine the association between the sociodemographic variable and the categories of knowledge, perception, and uptake of IPTp-SP. Analysis, was done using SPSS, and the p-value of less than 5% was considered statistically significant. Of the 303 nursing mothers sampled in this study, 265(87.5%) had heard about IPTp-SP of which 138(52.1%) had average knowledge of IPTp-SP. A total of 168(63.4%) had poor perception, and 168(64.6%) had adequate uptake (3-4 doses) of IPTp. Education was significantly associated with perception and uptake, with the majority of women who demonstrated excellent perception were those who had tertiary education (7, 6.35%, p = 0.05), and the majority who demonstrated excellent uptake (5 completed doses) were women who had tertiary education (47, 37.9%, p = 0.01). While knowledge was average, perception of IPTp-SP was poor for the majority of the nursing mothers which might have hampered their uptake of IPTp-SP during pregnancy. It is important that continuous assessment of the individual factors affecting the uptake of IPTp-SP be done regularly to curb the negative influences on the uptake of IPTp-SP.